Ultrasound efficacy of targeted-synthetic disease-modifying anti-rheumatic drug treatment in rheumatoid arthritis: a multicenter prospective cohort study in Japan. (4th July 2022) - Endo, Y; Kawashiri, S-Y; Nishino, A; Michitsuji, T; Tomokawa, T; Nishihata, S; Okamoto, M; Tsuji, Y; Tsuji, S; Shimizu, T; Sumiyoshi, R; Igawa, T; et al.
Abstract : Objective: This study investigated the effectiveness of treatment with Janus kinase (JAK) inhibitors in rheumatoid arthritis (RA) assessed by ultrasonography (US) activity, and the influence of patient characteristics and previous treatments. Method: This prospective study assessed 60 treatment initiations among 53 Japanese patients diagnosed with RA who underwent treatment with JAK inhibitors during June 2013 to February 2020. Of the 53 patients, seven patients were enrolled in duplicate because they were treated with two different JAK inhibitors at different periods. For each case, the improvement rate on the power Doppler (PD) score was assessed at 6 month follow-up. Median improvement rate of PD score was used to classify cases as either US responders or non-responders, and patient characteristics were compared between the two groups. Results: All indicators of clinical disease activity and US activity showed a significant improvement at 3 months compared with baseline. Although the JAK inhibitor-cycler group and the interleukin-6 (IL-6) inhibitor inadequate response (IR) group tended to show a later improvement for US activity, all indicators of clinical disease activity and US activity showed a significant improvement at 6 months compared with baseline for both groups. Multivariate analysis showed that concomitant methotrexate use and an IR to the previous biologic or targeted-synthetic disease-modifying anti-rheumatic drug (b/tsDMARD) treatment were independently and significantly associated with US responders. Conclusion: Use of a JAK inhibitor in combination with methotrexate and an absence of IR to any previous b/tsDMARDs demonstrated superior effectiveness for patients with RA.